An analysis of drug trafficking - Harper, Rosalyn (The British journal of criminology, 2000)
Examines the demographic and sentencing characteristics of traffickers caught smuggling drugs through Heathrow Airport between July 1991 and September 1997. Socio-demographic characteristics of the traffickers; Equity in their sentencing